(untitled) (Ibrahim Cardiac Medical Journal, 2017)
Objective: Types of ovarian tumour are widely divergent and no age group is immune from ovarian tumour; but certain ages are more vulnerable to develop certain types of tumours. By far, very few studies describing the histological types and subtypes of ovarian tumour in the context of Bangladeshi population have been conducted. The present study was intended to find the histological variants of ovarian tumours in our women. Methods: The present study was carried out in Dhaka Medical College Hospital between July 2001 to June 2002. The total number of patients admitted with a clinical diagnosis of ovarian tumour during the study period was 238, while the total number of gynaecological admissions was 3189. In the present study every alternate patients of ovarian tumour who consented to participate in the study were included as long as 110 cases were met. After admission, history and clinical presentation were recorded and every case was followed till discharge. Provisional diagnosis was made clinically and by ultrasound when 14 cases were excluded for they did not have ovarian tumour at all. The remaining 96 cases were operated and were confirmed by operative and histopathological findings. Results: In the present study proportion of ovarian tumours was 6.52% of all gynecological admissions. The mean age of the patients was found to be 39.5 ± 6.3 years. The peak age incidence of benign ovarian tumors was found to lie between 21-50 years. Malignant ovarian tumors, however was found more commonly after the age of 50 years. After histopathological confirmation of the precise nature of the 96 ovarian tumors, it was found that benign tumour comprised 77% of the cases with malignant tumors occurring in the rest 23%. Among them tumours of epithelial origin formed 70.8% of all ovarian tumors, germ cell tumors 25% and sex-cord stromal tumours made up 4.2%. Among the epithelial tumors, serous tumors were most frequently seen (61.7%), followed by mucinous tumors (35.3%). The percentage of benign serous cystadenomas was 35.5%. The ratio between serous and mucinous cystadenocarcinoma was almost 2:1. Germ cell tumour found in this study was of moderate frequency (25%). Among them 15.6% were mature teratoma (dermoid cyst) followed by 5.2% dysgerminoma. Endodermal sinus tumors were relatively low (3.1%) and there was a case of immature or malignant teratoma. Sex-cord-stromal tumours were of lowest frequency (4.2%) and classified as ovarian fibroma, granulosa-cell tumor and Krukenberg tumour. Conclusion: The study concluded that benign tumour comprised three-quarters of all ovarian tumours with the rest being malignant. Tumours of epithelial origin forms the main bulk, germ cell tumors about one-quarter and sex-cord stromal and metastatic tumors the least. Among the epithelial tumors, serous tumors were most frequently seen, followed by mucinous tumors. Ibrahim Card Med J 2015; 5 (1&2): 40-44